Help wanted: The drivers and implications of labour shortages - Martin Groiss; David Sondermann (European Central Bank (ECB), 2023)
Labour shortages have become prevalent across advanced economies. Yet, little is known about which firms are more likely to face them and the impact they have on the labour market. We create a firm-level data set spanning 28 EU countries, 283 regions and 18 sectors, contributing to close this gap. We find that structural factors play the dominant role. Firms in regions with limited labour supply as well as innovative and fast-growing firms are particularly prone to face labour shortages. Moreover, shortages tend to aggravate at business cycle peaks. In a second stage, we empirically determine the impact of labour shortages on wages and hiring. Firms with higher shortages pay a wage growth premium to keep and attract workers, increasingly so if they face excess demand. At the same time, those are the firms that hire less than the average.
Keywords: C36; E24; J20; J23; J30; 330; labour shortages; tightness; matching; shift-share instrument